Differences in characteristics between naturalized threatened plants and other threatened plants - Weihan Zhao; Trevor S. Fristoe; Amy J. S. Davis; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Petr Pyšek; Patrick Weigelt; Marten Winter; Mark van Kleunen (Conservation Biology, 2026)
Many non‐native plant species introduced by humans have become naturalized. At the same time many species are threatened in their native range. However, the number of plant species threatened in their native range that are naturalized elsewhere remains unknown. So too does the set of characteristics that distinguishes such species from other threatened species. For vascular plant species, we combined information from databases on threat status and naturalization success and information on growth forms, economic uses, and native and non‐native ranges to identify plants that are threatened in their native range but naturalized in their non‐native range. Among the 26,036 species assessed as threatened by the International Union for Conservation of Nature, only 238 (∼1%) were naturalized elsewhere. Most of the species threatened in their native range that are naturalized elsewhere were trees or shrubs of economic value, for example, for building materials and landscaping. More threatened species than expected were naturalized in Europe, and these include species from nearly all continents. Although Africa was the largest source of species threatened in their native range but naturalized elsewhere in absolute numbers, the numbers were lower than expected due to the continent's overall large number of threatened species. Only a few threatened plant species have become naturalized, and they differed in some of their characteristics, including growth form, native origin, threats, and economic use, from other threatened species.

The updated Global Naturalized Alien Flora ( GloNAF 2.0) database - Amy J. S. Davis; Wayne Dawson; Franz Essl; Holger Kreft; Bernd Lenzner; Jan Pergl; Petr Pyšek; Patrick Weigelt; Marten Winter; Mark van Kleunen (Ecology, 2025)
GloNAF is a continuously updated, curated compilation of alien naturalized vascular plant inventories for geographic regions worldwide. Building on its predecessor, GloNAF 2.0 now contains 16,429 taxa and introduces major updates, including the standardization of taxonomic names using the World Checklist of Vascular Plants (WCVP), removal of outdated records, and the net addition of 117,229 new records. These new entries have substantially increased the size of GloNAF, resulting in a 26% increase in the number of naturalized taxa in the database and a 31% increase in the number of geographic regions compared to GloNAF 1.2. We provide an overview of GloNAF 2.0, highlighting its expanded geographic and taxonomic coverage. In addition, we have aligned GloNAF with FAIR data principles through improvements in data accessibility, metadata standards, and support for data reuse. GloNAF 2.0 represents a significant and comprehensive resource for researchers aiming to advance our understanding of the drivers and consequences of biological invasions and naturalization success. The dataset is published under a CC‐BY 4.0 license; thus, when using these data, please give credit to this paper.

Gaps in Global Alien Plant Trait Data and How to Fill Them - Matthias Grenié; Helge Bruelheide; Wayne Dawson; Franz Essl; Mark van Kleunen; Ingolf Kühn; Holger Kreft; Petr Pyšek; Patrick Weigelt; Marten Winter (Global Ecology and Biogeography, 2025)
Aim Functional traits help to understand the ecological processes underlying biological invasions. The extent to which trait data are available for alien plants at the global scale is unknown. In this study, we assess the availability of trait data and identify global gaps and biases. Location Global. Time Period Present. Major Taxa Studied Vascular plants. Methods We used the GloNAF database to get a global list of plants naturalised outside their native range and their distributions. We combined data from the four largest trait databases: AusTraits, BIEN, GIFT, and TRY, on which we performed taxonomic and trait harmonisation. We studied the availability of trait data. Then, based on the distribution data, we tested to what extent trait knowledge was driven by ecological and socioeconomic variables. Results We found that the species‐by‐trait matrix (2764 traits for 14,539 species) was only 1.5% complete, with most traits measured for very few species. Only ten traits were available for more than 50% of all alien plants. Four percent of the species lacked all trait data, while 27% of species had data for the three key plant traits: leaf mass per area, seed mass, and plant height. We observed a strong latitudinal gradient in trait knowledge, with tropical regions showing lower trait knowledge than higher latitudes, particularly in the Northern Hemisphere. Growth form, range size, and invasion status were the strongest predictors of trait knowledge, with widespread, invasive tree species being better recorded than other alien species. Main Conclusions We identified large trait data gaps at a global scale for alien plants, which limits our ability to study functional invasion ecology at large spatial scales. These gaps are partly driven by uneven sampling and a lack of trait data integration across sources. We recommend prioritising the most invasion‐relevant traits and coordinating community efforts of plant and invasion scientists to sample them in a standardised way, which could help close these gaps.

Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.

Biogeography and global flows of 100 major alien fungal and fungus‐like oomycete pathogens - Anna Schertler; Bernd Lenzner; Stefan Dullinger; Dietmar Moser; Jennifer L. Bufford; Luisa Ghelardini; Alberto Santini; César Capinha; Miguel Monteiro; Luís Reino; Michael J. Wingfield; Hanno Seebens; et al. (Journal of Biogeography, 2024)
Aim Spreading infectious diseases associated with introduced pathogens can have devastating effects on native biota and human livelihoods. We analyse the global distribution of 100 major alien fungal and oomycete pathogens with substantial socio‐economic and environmental impacts and examine their taxonomy, ecological characteristics, temporal accumulation trajectories, regional hot‐ and coldspots of taxon richness and taxon flows between continents. Location Global. Taxon Alien/cryptogenic fungi and fungus‐like oomycetes, pathogenic to plants or animals. Methods To identify over/underrepresented classes and phyla, we performed Chi 2 tests of independence. To describe spatial patterns, we calculated the region‐wise richness and identified hot‐ and coldspots, defined as residuals after correcting taxon richness for region area and sampling effort via a quasi‐Poisson regression. We examined the relationship with environmental and socio‐economic drivers with a multiple linear regression and evaluated a potential island effect. Regional first records were pooled over 20‐year periods, and for global flows the links between the native range to the alien regions were mapped. Results Peronosporomycetes (Oomycota) were overrepresented among taxa and regional taxon richness was positively correlated with area and sampling effort. While no island effect was found, likely due to host limitations, hotspots were correlated with human modification of terrestrial land, per capita gross domestic product, temperate and tropical forest biomes, and orobiomes. Regional first records have increased steeply in recent decades. While Europe and Northern America were major recipients, about half of the taxa originate from Asia. Main Conclusions We highlight the putative importance of anthropogenic drivers, such as land use providing a conducive environment, contact opportunities and susceptible hosts, as well as economic wealth likely increasing colonisation pressure. While most taxa were associated with socio‐economic impacts, possibly partly due to a bias in research focus, about a third show substantial impacts to both socio‐economy and the environment, underscoring the importance of maintaining a wholescale perspective across natural and managed systems.

Phylogenetic structure of alien plant species pools from European donor habitats - Veronika Kalusová; Josep Padullés Cubino; Trevor S. Fristoe; Milan Chytrý; Mark van Kleunen; Wayne Dawson; Franz Essl; Holger Kreft; Ladislav Mucina; Jan Pergl; Petr Pyšek; Patrick Weigelt; et al. (Global Ecology and Biogeography, 2021)
Aim Many plant species native to Europe have naturalized worldwide. We tested whether the phylogenetic structure of the species pools of European habitats is related to the proportion of species from each habitat that has naturalized outside Europe (habitat’s donor role) and whether the donated species are more phylogenetically related to each other than expected by chance. Location Europe (native range), the rest of the world (invaded range). Time period Last c . 100 years. Major taxa studied Angiospermae. Methods We selected 33 habitats in Europe and analysed their species pools, including 9,636 plant species, of which 2,293 have naturalized outside Europe. We assessed the phylogenetic structure of each habitat as the difference between the observed and expected mean pairwise phylogenetic distance (MPD) for (a) the whole species pool and (b) subgroups of species that have naturalized outside Europe and those that have not. We used generalized linear models to test for the effects of the phylogenetic structure and the level of human influence on the habitat’s donor role. Results Habitats strongly to moderately influenced by humans often showed phylogenetically clustered species pools. Within the clustered species pools, those species that have naturalized outside Europe showed a random phylogenetic structure. Species pools of less human‐influenced natural habitats varied from phylogenetically clustered to overdispersed, with donated naturalized species also often showing random patterns within the species pools. Donor roles in both habitat groups increased with increasing MPD within habitats. Main conclusions European human‐influenced habitats donate closely related species that often naturalize in disturbed habitats outside their native range. Natural habitats donate species from different lineages with various ecological strategies that allow them to succeed in different habitats in the invaded range. However, the naturalized species donated by most European habitats are phylogenetically random subsets of their species pools.

Alternative futures for global biological invasions - Núria Roura-Pascual; Brian Leung; Wolfgang Rabitsch; Lucas Rutting; Joost Vervoort; Sven Bacher; Stefan Dullinger; Karl-Heinz Erb; Jonathan M. Jeschke; Stelios Katsanevakis; Ingolf Kühn; Bernd Lenzner; et al. (Sustainability Science, 2021)
Scenario analysis has emerged as a key tool to analyze complex and uncertain future socio-ecological developments. However, currently existing global scenarios (narratives of how the world may develop) have neglected biological invasions, a major threat to biodiversity and the economy. Here, we use a novel participatory process to develop a diverse set of global biological invasion scenarios spanning a wide range of plausible global futures through to 2050. We adapted the widely used “two axes” scenario analysis approach to develop four families of four scenarios each, resulting in 16 scenarios that were later clustered into four contrasting sets of futures. Our analysis highlights that socioeconomic developments and technological innovation have the potential to shape biological invasions, in addition to well-known drivers, such as climate and human land use change and global trade. Our scenarios partially align with the shared socioeconomic pathways created by the climate change research community. Several factors that drive differences in biological invasions were underrepresented in the shared socioeconomic pathways; in particular, the implementation of biosecurity policies. We argue that including factors related to public environmental awareness and technological and trade development in global scenarios and models is essential to adequately consider biological invasions in global environmental assessments and thereby obtain a more integrative picture of future social–ecological developments.

Persistent soil seed banks promote naturalisation and invasiveness in flowering plants - Margherita Gioria; Angelino Carta; Carol C. Baskin; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Mark van Kleunen; Patrick Weigelt; Marten Winter; Petr Pyšek (Ecology Letters, 2021)
With globalisation facilitating the movement of plants and seeds beyond the native range, preventing potentially harmful introductions requires knowledge of what drives the successful establishment and spread of alien plants. Here, we examined global‐scale relationships between naturalisation success (incidence and extent) and invasiveness, soil seed bank properties (type and densities) and key species traits (seed mass, seed dormancy and life form) for 2350 species of angiosperms. Naturalisation and invasiveness were strongly associated with the ability to form persistent (vs. transient) seed banks but relatively weakly with seed bank densities and other traits. Our findings suggest that seed bank persistence is a trait that better captures the ability to become naturalised and invasive compared to seed traits more widely available in trait databases. Knowledge of seed persistence can contribute to our ability to predict global naturalisation and invasiveness and to identify potentially invasive flowering plants before they are introduced.

Widespread decline in Central European plant diversity across six decades - David Eichenberg; Diana E. Bowler; Aletta Bonn; Helge Bruelheide; Volker Grescho; David Harter; Ute Jandt; Rudolf May; Marten Winter; Florian Jansen (Global Change Biology, 2021)
Based on plant occurrence data covering all parts of Germany, we investigated changes in the distribution of 2136 plant species between 1960 and 2017. We analyzed 29 million occurrence records over an area of ~350,000 km 2 on a 5 × 5 km grid using temporal and spatiotemporal models and accounting for sampling bias. Since the 1960s, more than 70% of investigated plant species showed declines in nationwide occurrence. Archaeophytes (species introduced before 1492) most strongly declined but also native plant species experienced severe declines. In contrast, neophytes (species introduced after 1492) increased in their nationwide occurrence but not homogeneously throughout the country. Our analysis suggests that the strongest declines in native species already happened in the 1960s–1980s, a time frame in which often few data exist. Increases in neophytic species were strongest in the 1990s and 2010s. Overall, the increase in neophytes did not compensate for the loss of other species, resulting in a decrease in mean grid cell species richness of −1.9% per decade. The decline in plant biodiversity is a widespread phenomenon occurring in different habitats and geographic regions. It is likely that this decline has major repercussions on ecosystem functioning and overall biodiversity, potentially with cascading effects across trophic levels. The approach used in this study is transferable to other large‐scale trend analyses using heterogeneous occurrence data.

Projecting the continental accumulation of alien species through to 2050 - Hanno Seebens; Sven Bacher; Tim M. Blackburn; César Capinha; Wayne Dawson; Stefan Dullinger; Piero Genovesi; Philip E. Hulme; Mark van Kleunen; Ingolf Kühn; Jonathan M. Jeschke; Bernd Lenzner; et al. (Global Change Biology, 2021)
Biological invasions have steadily increased over recent centuries. However, we still lack a clear expectation about future trends in alien species numbers. In particular, we do not know whether alien species will continue to accumulate in regional floras and faunas, or whether the pace of accumulation will decrease due to the depletion of native source pools. Here, we apply a new model to simulate future numbers of alien species based on estimated sizes of source pools and dynamics of historical invasions, assuming a continuation of processes in the future as observed in the past (a business‐as‐usual scenario). We first validated performance of different model versions by conducting a back‐casting approach, therefore fitting the model to alien species numbers until 1950 and validating predictions on trends from 1950 to 2005. In a second step, we selected the best performing model that provided the most robust predictions to project trajectories of alien species numbers until 2050. Altogether, this resulted in 3,790 stochastic simulation runs for 38 taxon–continent combinations. We provide the first quantitative projections of future trajectories of alien species numbers for seven major taxonomic groups in eight continents, accounting for variation in sampling intensity and uncertainty in projections. Overall, established alien species numbers per continent were predicted to increase from 2005 to 2050 by 36%. Particularly, strong increases were projected for Europe in absolute (+2,543 ± 237 alien species) and relative terms, followed by Temperate Asia (+1,597 ± 197), Northern America (1,484 ± 74) and Southern America (1,391 ± 258). Among individual taxonomic groups, especially strong increases were projected for invertebrates globally. Declining (but still positive) rates were projected only for Australasia. Our projections provide a first baseline for the assessment of future developments of biological invasions, which will help to inform policies to contain the spread of alien species.

Latitudinal patterns of alien plant invasions - Qinfeng Guo; Brian S. Cade; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Mark van Kleunen; Patrick Weigelt; Marten Winter; Petr Pyšek (Journal of Biogeography, 2021)
Latitudinal patterns of biodiversity have long been a central topic in ecology and evolutionary biology. However, while most previous studies have focused on native species, little effort has been devoted to latitudinal patterns of plant invasions (with a few exceptions based on data from sparse locations). Using the most up‐to‐date worldwide native and alien plant distribution data from 801 regions (including islands), we compared invasion levels (i.e. alien richness/total richness) in the Northern and Southern Hemispheres and across continental regions and islands around the globe. Results from quantile regressions using B‐splines to model nonlinearity showed (1) declining richness with increasing latitude, although the highest alien richness occurs at around 40 degrees in both hemispheres, (2) decreasing invasion levels towards higher latitudes on islands but a unimodal pattern in invasion level in continental regions in each hemisphere, (3) significantly higher invasion levels on islands than in continental regions and (4) a greater variability in invasion levels on islands at low latitudes than on high‐latitude islands. In continental regions, only the mid‐latitudes had high variability with both low and high invasion levels. Our findings identified latitudes with invasion hotspots where management is urgently needed, and latitudes with many areas of low invasions but high conservation potential where prevention of future invasions should be the priority.

Drivers of future alien species impacts: An expert‐based assessment - Franz Essl; Bernd Lenzner; Sven Bacher; Sarah Bailey; Cesar Capinha; Curtis Daehler; Stefan Dullinger; Piero Genovesi; Cang Hui; Philip E. Hulme; Jonathan M. Jeschke; Stelios Katsanevakis; et al. (Global Change Biology, 2020)
Understanding the likely future impacts of biological invasions is crucial yet highly challenging given the multiple relevant environmental, socio‐economic and societal contexts and drivers. In the absence of quantitative models, methods based on expert knowledge are the best option for assessing future invasion trajectories. Here, we present an expert assessment of the drivers of potential alien species impacts under contrasting scenarios and socioecological contexts through the mid‐21st century. Based on responses from 36 experts in biological invasions, moderate (20%–30%) increases in invasions, compared to the current conditions, are expected to cause major impacts on biodiversity in most socioecological contexts. Three main drivers of biological invasions—transport, climate change and socio‐economic change—were predicted to significantly affect future impacts of alien species on biodiversity even under a best‐case scenario. Other drivers (e.g. human demography and migration in tropical and subtropical regions) were also of high importance in specific global contexts (e.g. for individual taxonomic groups or biomes). We show that some best‐case scenarios can substantially reduce potential future impacts of biological invasions. However, rapid and comprehensive actions are necessary to use this potential and achieve the goals of the Post‐2020 Framework of the Convention on Biological Diversity.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Towards a macroscope: Leveraging technology to transform the breadth, scale and resolution of macroecological data - Maria Dornelas; Elizabeth M. P. Madin; Michael Bunce; Joseph D. DiBattista; Mark Johnson; Joshua S. Madin; Anne E. Magurran; Brian J. McGill; Nathalie Pettorelli; Oscar Pizarro; Stefan B. Williams; Marten Winter; et al. (Global Ecology and Biogeography, 2019)
The problem Earth‐based observations of the biosphere are spatially biased in ways that can limit our ability to detect macroecological patterns and changes in biodiversity. To resolve this problem, we need to supplement the ad hoc data currently collected with planned biodiversity monitoring, in order to approximate global stratified random sampling of the planet. We call this all‐encompassing observational system ‘the macroscope’. The solution With a focus on the marine realm, we identify seven main biosphere observation tools that compose the macroscope: satellites, drones, camera traps, passive acoustic samplers, biologgers, environmental DNA and human observations. By deploying a nested array of these tools that fills current gaps in monitoring, we can achieve a macroscope fit for purpose and turn these existing powerful tools into more than the sum of their parts. An appeal Building a macroscope requires commitment from many fields, together with coordinated actions to attract the level of funding required for such a venture. We call on macroecologists to become advocates for the macroscope and to engage with existing global observation networks.

Global mismatches in aboveground and belowground biodiversity - Erin K. Cameron; Inês S. Martins; Patrick Lavelle; Jérôme Mathieu; Leho Tedersoo; Mohammad Bahram; Felix Gottschall; Carlos A. Guerra; Jes Hines; Guillaume Patoine; Julia Siebert; Marten Winter; et al. (Conservation Biology, 2019)
Human activities are accelerating global biodiversity change and have resulted in severely threatened ecosystem services. A large proportion of terrestrial biodiversity is harbored by soil, but soil biodiversity has been omitted from many global biodiversity assessments and conservation actions, and understanding of global patterns of soil biodiversity remains limited. In particular, the extent to which hotspots and coldspots of aboveground and soil biodiversity overlap is not clear. We examined global patterns of these overlaps by mapping indices of aboveground (mammals, birds, amphibians, vascular plants) and soil (bacteria, fungi, macrofauna) biodiversity that we created using previously published data on species richness. Areas of mismatch between aboveground and soil biodiversity covered 27% of Earth's terrestrial surface. The temperate broadleaf and mixed forests biome had the highest proportion of grid cells with high aboveground biodiversity but low soil biodiversity, whereas the boreal and tundra biomes had intermediate soil biodiversity but low aboveground biodiversity. While more data on soil biodiversity are needed, both to cover geographic gaps and to include additional taxa, our results suggest that protecting aboveground biodiversity may not sufficiently reduce threats to soil biodiversity. Given the functional importance of soil biodiversity and the role of soils in human well‐being, soil biodiversity should be considered further in policy agendas and conservation actions by adapting management practices to sustain soil biodiversity and considering soil biodiversity when designing protected areas.

Contrasting patterns of naturalized plant richness in the Americas: Numbers are higher in the North but expected to rise sharply in the South - Petr Pyšek; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Hanno Seebens; Mark van Kleunen; Patrick Weigelt; Marten Winter (Global Ecology and Biogeography, 2019)
With increasing availability of plant distribution data, the information about global plant diversity is improving rapidly. Recently, Ulloa Ulloa et al. (2017) presented the first comprehensive overview of the native vascular flora of the Americas, yielding a total count of 124,993 native species. Of these, 51,241 occur in North America and 82,052 in South America. By combining these data with the information in the Global Naturalized Alien Flora (GloNAF) database of naturalized alien floras, we point out that for a complete picture of the regional and continental plant richness, the naturalized alien species need to be considered. Ignoring this novel component of regional floras can lead to an inaccurate picture of overall change in biodiversity in the Anthropocene. We show that North and South America might face contrasting challenges in terms of potential threats to biodiversity posed by alien plant species, because of the different past and present dynamics of invasions and predictions of future development. In total, there are 7,042 naturalized alien plants occurring in the Americas, with 6,122 recorded in North America and 2,677 in South America; if only introductions from other continents are considered additions to the native continental flora make up 6.9 and 1.4 %, respectively. Nevertheless, predictions of naturalized plant trajectories based on global trade dynamics and climate change suggest that considerable increases in naturalized plant numbers are expected in the next 20 years for emerging South American economies, which could reverse the present state.

Conventional land‐use intensification reduces species richness and increases production: A global meta‐analysis - Michael Beckmann; Katharina Gerstner; Morodoluwa Akin‐Fajiye; Silvia Ceaușu; Stephan Kambach; Nicole L. Kinlock; Helen R. P. Phillips; Willem Verhagen; Jessica Gurevitch; Stefan Klotz; Tim Newbold; Peter H. Verburg; et al. (Global Change Biology, 2019)
Most current research on land‐use intensification addresses its potential to either threaten biodiversity or to boost agricultural production. However, little is known about the simultaneous effects of intensification on biodiversity and yield. To determine the responses of species richness and yield to conventional intensification, we conducted a global meta‐analysis synthesizing 115 studies which collected data for both variables at the same locations. We extracted 449 cases that cover a variety of areas used for agricultural (crops, fodder) and silvicultural (wood) production. We found that, across all production systems and species groups, conventional intensification is successful in increasing yield (grand mean + 20.3%), but it also results in a loss of species richness (−8.9%). However, analysis of sub‐groups revealed inconsistent results. For example, small intensification steps within low intensity systems did not affect yield or species richness. Within high‐intensity systems species losses were non‐significant but yield gains were substantial (+15.2%). Conventional intensification within medium intensity systems revealed the highest yield increase (+84.9%) and showed the largest loss in species richness (−22.9%). Production systems differed in their magnitude of richness response, with insignificant changes in silvicultural systems and substantial losses in crop systems (−21.2%). In addition, this meta‐analysis identifies a lack of studies that collect robust biodiversity (i.e. beyond species richness) and yield data at the same sites and that provide quantitative information on land‐use intensity. Our findings suggest that, in many cases, conventional land‐use intensification drives a trade‐off between species richness and production. However, species richness losses were often not significantly different from zero, suggesting even conventional intensification can result in yield increases without coming at the expense of biodiversity loss. These results should guide future research to close existing research gaps and to understand the circumstances required to achieve such win‐win or win‐no‐harm situations in conventional agriculture.

Autofertility and self‐compatibility moderately benefit island colonization of plants - Mialy Razanajatovo; Mark van Kleunen; Holger Kreft; Wayne Dawson; Franz Essl; Jan Pergl; Petr Pyšek; Marten Winter; Patrick Weigelt (Global Ecology and Biogeography, 2019)
Aim The current geographical distribution of species largely reflects colonization success after natural long‐distance dispersal or introduction by humans. Plants with selfing ability should have an advantage when establishing on islands where mates and pollinators are limited (Baker’s law). However, high percentages of dioecious and self‐incompatible species have been reported for some islands, possibly resulting from post‐colonization evolution. Given that such evolution is less likely to apply to alien species recently introduced to islands by humans, tests of Baker’s law on islands need to consider both native and naturalized alien species. Location Global. Time period Undefined. Major taxa studied Angiosperms. Methods To test whether the colonization of islands is associated with selfing ability (self‐compatibility and autofertility), we combined three comprehensive global databases: one on breeding systems of species, one on island and mainland distributions of native species and one on global naturalization of alien plants. We assigned each of a total of 1,752 species, from 161 angiosperm families, as mainland species, island colonists and/or island endemics (i.e., species that are restricted to islands). To assess potential relationships between island occurrence and selfing ability of species, we used multinomial logistic regressions. Results We found that species with high selfing ability were slightly more likely to be island colonist than mainland species. However, selfing ability did not increase the likelihood of being an island endemic in contrast to mainland species. Among island colonists, selfing ability did not differ between species on oceanic and on continental islands or between species native to islands and naturalized on islands. Main conclusions We performed a comprehensive test of Baker’s law by considering many angiosperm families, using continuous metrics of self‐compatibility and autofertility and including both native and naturalized species. We provide global evidence that high selfing ability may foster island colonization of angiosperms.

Tall-statured grasses: a useful functional group for invasion science - Susan Canavan; Laura A. Meyerson; Jasmin G. Packer; Petr Pyšek; Noëlie Maurel; Vanessa Lozano; David M. Richardson; Giuseppe Brundu; Kim Canavan; Angela Cicatelli; Jan Čuda; Wayne Dawson; et al. (Biological Invasions, 2019)

The Global Naturalized Alien Flora (Glo NAF ) database - Mark van Kleunen; Petr Pyšek; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Patrick Weigelt; Anke Stein; Stefan Dullinger; Christian König; Bernd Lenzner; Noëlie Maurel; et al. (Ecology, 2019)
This dataset provides the Global Naturalized Alien Flora (Glo NAF ) database, version 1.2. Glo NAF represents a data compendium on the occurrence and identity of naturalized alien vascular plant taxa across geographic regions (e.g. countries, states, provinces, districts, islands) around the globe. The dataset includes 13,939 taxa and covers 1,029 regions (including 381 islands). The dataset is based on 210 data sources. For each taxon‐by‐region combination, we provide information on whether the taxon is considered to be naturalized in the specific region (i.e. has established self‐sustaining populations in the wild). Non‐native taxa are marked as “alien”, when it is not clear whether they are naturalized. To facilitate alignment with other plant databases, we provide for each taxon the name as given in the original data source and the standardized taxon and family names used by The Plant List Version 1.1 ( http://www.theplantlist.org/ ). We provide an ESRI shapefile including polygons for each region and information on whether it is an island or a mainland region, the country and the Taxonomic Databases Working Group ( TDWG ) regions it is part of ( TDWG levels 1–4). We also provide several variables that can be used to filter the data according to quality and completeness of alien taxon lists, which vary among the combinations of regions and data sources. A previous version of the Glo NAF dataset (version 1.1) has already been used in several studies on, for example, historical spatial flows of taxa between continents and geographical patterns and determinants of naturalization across different taxonomic groups. We intend the updated and expanded Glo NAF version presented here to be a global resource useful for studying plant invasions and changes in biodiversity from regional to global scales. We release these data into the public domain under a Creative Commons Zero license waiver ( https://creativecommons.org/share-your-work/public-domain/cc0/ ). When you use the data in your publication, we request that you cite this data paper. If Glo NAF is a major part of the data analyzed in your study, you should consider inviting the Glo NAF core team (see Metadata S1: Originators in the Overall project description) as collaborators. If you plan to use the Glo NAF dataset, we encourage you to contact the Glo NAF core team to check whether there have been recent updates of the dataset, and whether similar analyses are already ongoing.

The role of adaptive strategies in plant naturalization - Wen‐Yong Guo; Mark van Kleunen; Marten Winter; Patrick Weigelt; Anke Stein; Simon Pierce; Jan Pergl; Dietmar Moser; Noëlie Maurel; Bernd Lenzner; Holger Kreft; Franz Essl; et al. (Ecology Letters, 2018)
Determining the factors associated with the naturalization of alien species is a central theme in ecology. Here, we tested the usefulness of a metric for quantifying Grime's seminal concept of adaptive strategies – competitors, stress‐tolerators and ruderals ( CSR ) – to explain plant naturalizations worldwide. Using a global dataset of 3004 vascular plant species, and accounting for phylogenetic relatedness and species’ native biomes, we assessed the associations between calculated C‐, S‐ and R‐scores and naturalization success for species exhibiting different life forms. Across different plant life forms, C‐scores were positively and S‐scores negatively associated with both the probability of naturalization and the number of regions where the species has naturalized. R‐scores had positive effects on the probability of naturalization. These effects of the scores were, however, weak to absent for tree species. Our findings demonstrate the utility of CSR ‐score calculation to broadly represent, and potentially explain, the naturalization success of plant species.

Spatial scaling of extinction rates: Theory and data reveal nonlinearity and a major upscaling and downscaling challenge - Petr Keil; Henrique M. Pereira; Juliano S. Cabral; Jonathan M. Chase; Felix May; Inês S. Martins; Marten Winter (Global Ecology and Biogeography, 2018)
Aim Biodiversity loss is a key component of biodiversity change and can impact ecosystem services. However, estimation of the loss has focused mostly on per‐species extinction rates measured over a limited number of spatial scales, with little theory linking small‐scale extirpations to global extinctions. Here, we provide such a link by introducing the relationship between area and the number of extinctions (number of extinctions–area relationship; NxAR) and between area and the proportion of extinct species (proportion of extinctions–area relationship; PxAR). Unlike static patterns, such as the species–area relationship, NxAR and PxAR represent spatial scaling of a dynamic process. We show theoretical and empirical forms of these relationships and we discuss their role in perception and estimation of the current extinction crisis. Location U.S.A., Europe, Czech Republic and Barro Colorado Island (Panama). Time period 1500–2009. Major taxa studied Vascular plants, birds, butterflies and trees. Methods We derived the expected forms of NxAR and PxAR from several theoretical frameworks, including the theory of island biogeography, neutral models and species–area relationships. We constructed NxAR and PxAR from five empirical datasets collected over a range of spatial and temporal scales. Results Although increasing PxAR is theoretically possible, empirical data generally support a decreasing PxAR; the proportion of extinct species decreases with area. In contrast, both theory and data revealed complex relationships between numbers of extinctions and area (NxAR), including nonlinear, unimodal and U‐shaped relationships, depending on region, taxon and temporal scale. Main conclusions The wealth of forms of NxAR and PxAR explains why biodiversity change appears scale dependent. Furthermore, the complex scale dependence of NxAR and PxAR means that global extinctions indicate little about local extirpations, and vice versa. Hence, effort should be made to understand and report extinction rates as a scale‐dependent problem. In this effort, estimation of scaling relationships such as NxAR and PxAR should be central.

Naturalization of ornamental plant species in public green spaces and private gardens - Katharina Mayer; Emily Haeuser; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Petr Pyšek; Patrick Weigelt; Marten Winter; Bernd Lenzner; Mark van Kleunen (Biological Invasions, 2017)

A world of sequences: can we use georeferenced nucleotide databases for a robust automated phylogeography? - Paolo Gratton; Silvio Marta; Gaëlle Bocksberger; Marten Winter; Emiliano Trucchi; Hjalmar Kühl (Journal of Biogeography, 2017)
Aim Comparative phylogeography across a large number of species allows investigating community‐level processes at regional and continental scales. An effective approach to such studies would involve automatic retrieval of georeferenced sequence data from nucleotide databases (a first step towards an ‘automated phylogeography’). It remains unclear if, despite repeated calls, georeferencing of nucleotide databases has increased in frequency, and if accumulated data allow for broad applications based on automated retrieval of sequence data and associated geographical information. Here, we investigated geographical information available in NCBI GenBank accessions for tetrapods, exploring temporal and geographical patterns in georeferencing, and quantifying data available for automated phylogeography. Location Global. Methods We developed Python and R scripts to (1) download metadata from GenBank (1,125,514 accessions, > 20,000 species); (2) geocode accessions from associated metadata; (3) map originally georeferenced and geocoded accessions and plot their frequency against time; (4) assess the size of intraspecific sets of homologous sequences and compare their geographical extent with species ranges, thus evaluating their potential for phylogeographical analyses. Results Only 6.2% of surveyed tetrapod GenBank submissions reported geographical coordinates, without increase in recent years. Our geocoding raised georeferenced accessions to 15.1%. The geographical distribution of georeferenced accessions is patchy, and especially sparse in economically underdeveloped areas. Automatically retrievable informative data sets covering most of the range are available for very few species of wide‐ranging tetrapods. Main conclusions Although geocoding offers a partial solution to the scarcity of direct georeferencing, the amount of data potentially useful for automated phylogeography is still limited. Strong underrepresentation of hard‐to‐access areas suggests that sampling logistics represent a main hindrance to global data availability. We propose that, besides enhancing georeferencing of genetic data, future research agendas should focus on collaborative efforts to sample genetic diversity in biodiversity‐rich tropical areas.

Climate change will increase the naturalization risk from garden plants in Europe - Iwona Dullinger; Johannes Wessely; Oliver Bossdorf; Wayne Dawson; Franz Essl; Andreas Gattringer; Günther Klonner; Holger Kreft; Michael Kuttner; Dietmar Moser; Jan Pergl; Petr Pyšek; et al. (Global Ecology and Biogeography, 2017)
Aim Plant invasions often follow initial introduction with a considerable delay. The current non‐native flora of a region may hence contain species that are not yet naturalized but may become so in the future, especially if climate change lifts limitations on species spread. In Europe, non‐native garden plants represent a huge pool of potential future invaders. Here, we evaluate the naturalization risk from this species pool and how it may change under a warmer climate. Location Europe. Methods We selected all species naturalized anywhere in the world but not yet in Europe from the set of non‐native European garden plants. For this subset of 783 species, we used species distribution models to assess their potential European ranges under different scenarios of climate change. Moreover, we defined geographical hotspots of naturalization risk from those species by combining projections of climatic suitability with maps of the area available for ornamental plant cultivation. Results Under current climate, 165 species would already find suitable conditions in > 5% of Europe. Although climate change substantially increases the potential range of many species, there are also some that are predicted to lose climatically suitable area under a changing climate, particularly species native to boreal and Mediterranean biomes. Overall, hotspots of naturalization risk defined by climatic suitability alone, or by a combination of climatic suitability and appropriate land cover, are projected to increase by up to 102% or 64%, respectively. Main conclusions Our results suggest that the risk of naturalization of European garden plants will increase with warming climate, and thus it is very likely that the risk of negative impacts from invasion by these plants will also grow. It is therefore crucial to increase awareness of the possibility of biological invasions among horticulturalists, particularly in the face of a warming climate.

Global trade will accelerate plant invasions in emerging economies under climate change - Hanno Seebens; Franz Essl; Wayne Dawson; Nicol Fuentes; Dietmar Moser; Jan Pergl; Petr Pyšek; Mark van Kleunen; Ewald Weber; Marten Winter; Bernd Blasius (Global Change Biology, 2015)
Trade plays a key role in the spread of alien species and has arguably contributed to the recent enormous acceleration of biological invasions, thus homogenizing biotas worldwide. Combining data on 60‐year trends of bilateral trade, as well as on biodiversity and climate, we modeled the global spread of plant species among 147 countries. The model results were compared with a recently compiled unique global data set on numbers of naturalized alien vascular plant species representing the most comprehensive collection of naturalized plant distributions currently available. The model identifies major source regions, introduction routes, and hot spots of plant invasions that agree well with observed naturalized plant numbers. In contrast to common knowledge, we show that the ‘imperialist dogma,’ stating that Europe has been a net exporter of naturalized plants since colonial times, does not hold for the past 60 years, when more naturalized plants were being imported to than exported from Europe. Our results highlight that the current distribution of naturalized plants is best predicted by socioeconomic activities 20 years ago. We took advantage of the observed time lag and used trade developments until recent times to predict naturalized plant trajectories for the next two decades. This shows that particularly strong increases in naturalized plant numbers are expected in the next 20 years for emerging economies in megadiverse regions. The interaction with predicted future climate change will increase invasions in northern temperate countries and reduce them in tropical and (sub)tropical regions, yet not by enough to cancel out the trade‐related increase.

Alien plants invade more phylogenetically clustered community types and cause even stronger clustering - Zdeňka Lososová; Francesco de Bello; Milan Chytrý; Ingolf Kühn; Petr Pyšek; Jiří Sádlo; Marten Winter; David Zelený (Global Ecology and Biogeography, 2015)
Aim Several hypotheses postulate that species invasion is affected by an interplay between the phylogenetic position of the invading species and the phylogenetic structure of the invaded community type. Some of them suggest that phylogenetic relatedness of invaders to native species promotes naturalization, because phylogenetically related alien species tend to have similar environmental adaptations as native species. Others predict that phylogenetic relatedness hampers naturalization because of stronger competition of aliens with native species and shared enemies. Here we ask how phylogenetic diversity of native species affects invasion across community types. Location C zech R epublic. Methods All major plant community types at a national scale ( n = 88) were characterized by their species pools, i.e. lists of species that can potentially occur there. Of the total number of 2306 species, 1785 were native, 246 were archaeophytes and 275 were neophytes. For each species pool, we related the number of alien species to the phylogenetic diversity of the native species pool, calculated as mean phylogenetic distance ( MPD ) and mean nearest taxon distance ( MNTD ), including null models. Results The number of alien species was related both to the phylogenetic structure of community types and to the phylogenetic position of alien species. Frequently disturbed herbaceous community types with strong phylogenetic clustering were more invaded than others, possibly due to disturbance acting as an environmental filter. Here, alien species increased the degree of phylogenetic clustering as they tended to be from the same lineages as native species. Such trends were not detected for phylogenetically more diverse community types such as forests. Main conclusions Our findings support the hypothesis that relatedness of invaders to native species promotes invasion because of their shared adaptations to the same environments. Alien species more strongly invade community types that are phylogenetically clustered, and because they tend to be related to native species, invaded community types become even more clustered.

Defining the Impact of Non‐Native Species - JONATHAN M. JESCHKE; SVEN BACHER; TIM M. BLACKBURN; JAIMIE T. A. DICK; FRANZ ESSL; THOMAS EVANS; MIRIJAM GAERTNER; PHILIP E. HULME; INGOLF KÜHN; AGATA MRUGAŁA; JAN PERGL; PETR PYŠEK; et al. (Conservation Biology, 2014)
Non‐native species cause changes in the ecosystems to which they are introduced. These changes, or some of them, are usually termed impacts; they can be manifold and potentially damaging to ecosystems and biodiversity. However, the impacts of most non‐native species are poorly understood, and a synthesis of available information is being hindered because authors often do not clearly define impact. We argue that explicitly defining the impact of non‐native species will promote progress toward a better understanding of the implications of changes to biodiversity and ecosystems caused by non‐native species; help disentangle which aspects of scientific debates about non‐native species are due to disparate definitions and which represent true scientific discord; and improve communication between scientists from different research disciplines and between scientists, managers, and policy makers. For these reasons and based on examples from the literature, we devised seven key questions that fall into 4 categories: directionality, classification and measurement, ecological or socio‐economic changes, and scale. These questions should help in formulating clear and practical definitions of impact to suit specific scientific, stakeholder, or legislative contexts. Definiendo el Impacto de las Especies No‐Nativas

Beta diversity of urban floras among E uropean and non‐ E uropean cities - Frank A. La Sorte; Myla F. J. Aronson; Nicholas S. G. Williams; Laura Celesti‐Grapow; Sarel Cilliers; Bruce D. Clarkson; Rebecca W. Dolan; Andrew Hipp; Stefan Klotz; Ingolf Kühn; Petr Pyšek; Stefan Siebert; et al. (Global Ecology and Biogeography, 2014)
Aim Cities represent an ideal study system for assessing how intensive land‐use change and biotic interchange have altered beta diversity at broad geographic extents. Here we test the hypothesis that floras in cities located in disparate regions of the globe are being homogenized by species classified as invasive (naturalized species that have spread over a large area) or as a E uropean archaeophyte (species introduced into E urope before ad 1500 from the M editerranean Basin). We also test the prediction that the global influences of European activities (colonization, agriculture, commerce) have supported this outcome. Location One hundred and ten cities world‐wide. Methods We examined the richness and composition of urban floras among E uropean ( n = 85) and non‐ E uropean cities ( n = 25) for species classified as native or non‐native, or further classified as E uropean archaeophyte or invasive. We modelled how geographic, climatic and anthropogenic factors were related to compositional similarity between E uropean and non‐ E uropean cities. Results We found that most plants in the cities we examined, particularly non‐ E uropean cities, were native and unique to each city. Non‐native species were similarly unique, but occurred in much lower proportions relative to natives. Although E uropean archaeophytes and invasive species also occurred in lower proportions, they had similar compositions among cities. E uropean archaeophytes were most prevalent in E uropean cities, but were most similar among non‐ E uropean cities. Contrasting E uropean and non‐ E uropean cities, geography and climate were most relevant for native and invasive species, whereas climate and agriculture were most relevant for E uropean archaeophytes. Main conclusions Cities in disparate regions of the globe retain regionally distinct native and non‐native plant assemblages, while invasive species, and especially E uropean archaeophytes, were associated with lower beta diversity among cities. These findings suggest that intensive land‐use change and biotic interchange, shaped through E uropean influences, have had a world‐wide effect on the beta diversity of urban plant assemblages.

Widespread plant species: natives versus aliens in our changing world - Thomas J. Stohlgren; Petr Pyšek; John Kartesz; Misako Nishino; Aníbal Pauchard; Marten Winter; Joan Pino; David M. Richardson; John R. U. Wilson; Brad R. Murray; Megan L. Phillips; Li Ming-yang; et al. (Biological Invasions, 2011)

The role of non‐native plants and vertebrates in defining patterns of compositional dissimilarity within and across continents - Marten Winter; Ingolf Kühn; Frank A. La Sorte; Oliver Schweiger; Wolfgang Nentwig; Stefan Klotz (Global Ecology and Biogeography, 2010)
Aim Human activities have led to the spread and establishment of increasing numbers of non‐native species. Here we assess whether non‐native plant and vertebrate species have affected species compositions within and across Europe and North America. We also assess the effects of intra‐continental species exchange using the example of vertebrates. Location European countries and North America (states in the contiguous United States and provinces of Canada). Methods We measured compositional dissimilarity of native and non‐native assemblages of vascular plants and vertebrates and related these patterns to climatic dissimilarity and geographical distance. We considered three categories of non‐native species (introduced after ad 1500), namely: those (1) originating outside of both continents, (2) native to one continent and non‐native to the other, and (3) native in a particular region of a continent but non‐native in another region. Results The presence of non‐native plants and vertebrates led to more homogeneous species compositions between continents and to less homogeneous species composition within Europe compared with the native assemblages. In North America, the presence of non‐native plants led to more homogeneous species compositions and the presence of non‐native vertebrates had no effect. Species compositions being more homogeneous than the native composition were found for the three categories of non‐native vertebrate species for both continents. Between continents, climate was a better predictor of compositional dissimilarity for non‐native plants, whereas for vertebrates the explanatory power of climate and geographical distance were comparable. By contrast, within continents, climate was a better predictor of compositional dissimilarity of both plants and vertebrates. Conclusions We found clear evidence for biotic homogenization as a consequence of species displacement. However, in relation to overall species richness this effect was rather small, indicating that floras and faunas are still quite distinct. Therefore, claiming that we already face homogeneous biotas might be premature, although clear indications are visible which should raise a note of caution, especially in the light of increasing globalization.

Spatial aspects of trait homogenization within the German flora - Marten Winter; Ingolf Kühn; Wolfgang Nentwig; Stefan Klotz (Journal of Biogeography, 2008)
Aim Biotic homogenization, the replacement of local biota by non‐indigenous and locally expanding species, is among the major effects of species invasions. Almost all studies related to this topic are focused on the species level, on taxonomic homogenization. Homogenization effects on trait diversity (functional homogenization) may be very important for ecosystem functioning, but they are rarely analysed, especially not at different spatial scales within a single study. This paper aims to examine how the presence of alien species (species introduced since 1500 ad ) affects the distribution of ploidy levels in the German flora at different spatial scales. Location Germany. Methods We used a resampling method and the Morisita–Horn dissimilarity index to calculate dissimilarities of ploidy level within and between alien and indigenous plants at three different spatial scales in Germany: (1) the entire country as one location, (2) between grid cells, and (3) within grid cells of a lattice covering Germany. Results We found a significant differentiation effect within grid cells of c. 130 km 2 , with alien plants increasing the variability of ploidy levels. The differentiation effect varies according to the scale used. At the coarsest scale (entire Germany), ploidy levels of alien plants tend to be more homogeneous in composition compared with those of native plants. At the intermediate scale (between grid cells), and even more pronounced at a small scale (within grid cells), ploidy levels are more heterogeneously distributed across Germany than those of native plant species. Main conclusions Homogenization of ploidy levels at a large scale (entire Germany) and differentiation at a small scale (within grid cells) is comparable with the patterns found in taxonomic homogenization analyses. This analysis is a first step towards understanding the impacts of plant invasions on a trait level. Differentiation and homogenization of ploidy levels might mirror the distribution of related ecological traits and therefore might have an impact on ecosystem functioning.